2021
DOI: 10.1021/acsfoodscitech.0c00161
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Oxidative Stability of Wholegrain Flours Using Nontargeted Ultraperformance Liquid Chromatography Coupled with Electrospray Ionization Quadrupole Time-of-Flight (UPLC-ESI-QTOF) Metabolomics

Abstract: Lipid stability is one of the major determinants of the quality of wholegrain wheat flours. Wheat grains contain a wide range of metabolites, many of which have antioxidant activities and can inhibit lipid oxidation. Metabolomics offers an opportunity for a broad understanding of the metabolite profiles of wheat germplasm resources. In this study, untargeted liquid chromatography mass spectrometry was used to investigate the metabolite diversity of 65 European wheat varieties. The wheat varieties showed variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
(109 reference statements)
0
1
0
Order By: Relevance
“…Of note, change in hexadecanedioic acid level was reported to be related to inflammatory status, and it contributed to the classification of SCZ and HCs in previous studies ( Cui et al, 2020 ; Qian et al, 2021 ). The diacylglyceryl-N,N,N-trimethylhomoserine (DGTS)16:0/18:1 level is considered a biomarker reflecting low oxidative stability among wheat varieties ( Wei et al, 2021 ). A meta-analysis has revealed that first-episode psychiatric patients exhibited a proinflammatory and vulnerable antioxidant status ( Fraguas et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, change in hexadecanedioic acid level was reported to be related to inflammatory status, and it contributed to the classification of SCZ and HCs in previous studies ( Cui et al, 2020 ; Qian et al, 2021 ). The diacylglyceryl-N,N,N-trimethylhomoserine (DGTS)16:0/18:1 level is considered a biomarker reflecting low oxidative stability among wheat varieties ( Wei et al, 2021 ). A meta-analysis has revealed that first-episode psychiatric patients exhibited a proinflammatory and vulnerable antioxidant status ( Fraguas et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%